Rotor UMP characteristics and vibration properties in synchronous generator due to 3D static air‐gap eccentricity faults. Issue 6 (19th March 2020) - He, Yu‐Ling; Sun, Yue‐Xin; Xu, Ming‐Xing; Wang, Xiao‐Long; Wu, Yu‐Cai; Vakil, Gaurang; Gerada, David; Gerada, Chris
Abstract : In this article, the qualitative theoretical derivation, together with finite element analysis and experimental studies are presented to investigate the unbalanced magnetic pull (UMP) as well as the rotor vibration characteristics. Differently from previous studies, this study focuses on the UMP/vibration not only under the normal and the conventional radial rotor eccentricity conditions but also for three‐dimensional (3D) hybrid static air‐gap eccentricity (SAGE) cases which are composed of both the radial SAGE and the axial SAGE. The detailed UMP expressions before and after each SAGE, are first deduced based on the analysis of the magnetic flux density variation. Then, the 3D finite element calculation and the experimental study are carried out on the CS‐5 prototype generator which has two poles and a rated speed of 3000 rpm in order to validate the proposed theoretical analysis. It is shown that the DC component and the even harmonics of the radial UMP/vibration, especially the second harmonic, increase under the SAGE conditions. Specifically, the increment of the radial SAGE increases both the radial and the axial UMPs/vibrations, while the growth of the axial SAGE increases the axial UMP/vibration but meanwhile reduces the radial UMP/vibration.